Inhibition of Exosome Release Alleviates Cognitive Impairment After Repetitive Mild Traumatic Brain Injury - Hu, Tianpeng; Han, Zhaoli; Xiong, Xiangyang; Li, Meimei; Guo, Mengtian; Yin, Zhenyu; Wang, Dong; Cheng, Lu; Li, Dai; Zhang, Shishuang; Wang, Lu; Zhao, Jing; et al. (Frontiers in Cellular Neuroscience, 2022)
Background Repetitive mild traumatic brain injury (rmTBI) is closely associated with chronic traumatic encephalopathy (CTE). Neuroinflammation and neuropathological protein accumulation are key links to CTE progression. Exosomes play important roles in neuroinflammation and neuropathological protein accumulation and spread. Here, we explored the role of brain-derived exosomes (BDEs) in mice with rmTBI and how the inhibition of BDE release contributes to neuroprotection. Methods GW4869 was used to inhibit exosome release, and behavioural tests, PET/CT and western blotting were conducted to explore the impact of this inhibition from different perspectives. We further evaluated cytokine expression by Luminex and microglial activation by immunofluorescence in mice with rmTBI after exosome release inhibition. Results Inhibition of BDE release reversed cognitive impairment in mice with rmTBI, enhanced glucose uptake and decreased neuropathological protein expression. Inhibition of BDE release also changed cytokine production trends and enhanced microglial proliferation. Conclusion In this study, we found that BDEs are key factor in cognitive impairment in mice with rmTBI and that microglia are the main target of BDEs. Thus, inhibition of exosome release may be a new strategy for improving CTE prognoses.